Peningkatan Komitmen Organisasi Dipengaruhi Work Family Conflict Melalui Kepuasan Kerja - MUSTOFA, WILDAN; FRIANTO, AGUS (Jurnal Ilmu Manajemen (JIM), 2019)
Companies in Indonesia are facing business challenges, namely the high intensity of competition among businesspeople. In addition, the company also wants their employees to be committed to the organization. One of thesecompanies was PT Perkebunan Nusantara XII which proved that PTPN XII Directors employees showed a highcommitment to the organization, because they were willing to be transferred to the Board of Directors Office,which was far from their place of residence and had to leave their families. The purpose of this study is to testand analyze the effect of Work Family Conflict on Organizational Commitment Through Job Satisfaction. Thisresearch is a causality study with a quantitative approach. The sampling technique in this study used a saturatedsample with a total of 50 respondents to the employees of PTPN XII Surabayas board of directors. The statisticalanalysis used in this study is Partial Least Square (PLS) with the help of smart PLS 3.0 software. The results ofthis study explain that Work Family Conflict has a negative effect on job satisfaction. Work Family Conflict doesnot affect organizational commitment. Job satisfaction has a positive effect on organizational commitment. Jobsatisfaction does not affect the relationship between Work Family Conflict to organizational commitment to PTPNXII Directors office employees.Keywords: job satisfaction; organizational commitment; work family conflict.